Targeted: Beirut : the 1983 Marine Barracks bombing and the untold origin story of the war on terror - Carr, Jack (Joint pseudonym); Scott, James (James M.) (Emily Bestler Books, Atria, 2024)
Based on comprehensive interviews with survivors, extensive military records, as well as personal letters, diaries and photographs, the full story is revealed behind the deadly truck bomb that exploded at the U.S. Marine Corp barracks in Beirut, Lebanon in 1983.